2021
DOI: 10.1111/tbed.14413
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic investigations of Streptococcus pasteurianus , an underreported zoonotic pathogen, isolated from a diseased piglet with meningitis

Abstract: Streptococcus pasteurianus, an underreported opportunistic pathogen, is considered an increasingly recognized cause of meningitis and bacteremia in many animals and humans worldwide. However, except for some epidemiological studies, there is no report about the gene‐deletion mutagenesis, virulence factors, reservoir niches or animal infection models for this pathogen. In this study, we first isolated an S. pasteurianus strain from a newly weaned piglet's brain with meningitis. The genomic sequence of this swin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 65 publications
0
10
0
Order By: Relevance
“…We found that both amphixenoses and anthropozoonoses are present equally often in deer populations, although anthropozoonoses were significantly more prevalent within populations. However, amphixenoses are largely underreported in the literature, which may contribute to the lower prevalence estimate for these pathogens (Duquette & Nuttell 2004, Wang et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…We found that both amphixenoses and anthropozoonoses are present equally often in deer populations, although anthropozoonoses were significantly more prevalent within populations. However, amphixenoses are largely underreported in the literature, which may contribute to the lower prevalence estimate for these pathogens (Duquette & Nuttell 2004, Wang et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“… C. coli can be a cause of foodborne illness in humans ( 51 ) and carried by healthy pigs while S . pasteurianus is an opportunistic pathogen in humans and has been associated with meningitis in piglets ( 52 ). In addition, certain MAGs contained more than one ARG on the same contig, suggesting that the ARGs are linked.…”
Section: Discussionmentioning
confidence: 99%
“…The volume of the white pulp was reduced, and the number of red blood cells was reduced. In the white pulp area, fragments of nuclei of necrotic cells were scattered, and white blood cells disappeared in part of the pulp area (S. Wang et al, 2022). In the red pulp area, the structure was blurred, the contour of capillaries was unclear, the number of lymphocytes was reduced, and there was a large amount of cellulose dispersed in the spleen tissue, which contained neutrophils.…”
Section: вісник сумського національного аграрного університетуmentioning
confidence: 99%